2019
DOI: 10.1007/978-3-030-20671-0_25
|View full text |Cite
|
Sign up to set email alerts
|

The Privacy Paradox of Utilizing the Internet of Things and Wi-Fi Tracking in Smart Cities

Abstract: In recent years, we have seen the increase of Internet of Things (IoT) solutions, products and services. The Internet of Things will capture a large amount of data pertaining from the environment, as well as their users. The real value of collecting data will be the result of data processing and aggregation in a large-scale where new knowledge can be extracted. However, such procedures can also lead to user privacy issues. This study describes what citizens do and do not know about Wi-Fi tracking and how that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 48 publications
0
0
0
Order By: Relevance
“…These deployments have garnered significant media attention, sparking discussions about privacy implications and the commercial utilization of tracking information. Studies like Ten et al [57] shed light on citizens' awareness (or lack thereof) regarding Wi-Fi tracking and how such awareness influences their responses to privacy and security risks. The findings revealed that most respondents were willing to cooperate with Wi-Fi tracking despite concerns about losing control over their data.…”
Section: Impact Of Rcm On Wi-fi Services and Proceduresmentioning
confidence: 99%
“…These deployments have garnered significant media attention, sparking discussions about privacy implications and the commercial utilization of tracking information. Studies like Ten et al [57] shed light on citizens' awareness (or lack thereof) regarding Wi-Fi tracking and how such awareness influences their responses to privacy and security risks. The findings revealed that most respondents were willing to cooperate with Wi-Fi tracking despite concerns about losing control over their data.…”
Section: Impact Of Rcm On Wi-fi Services and Proceduresmentioning
confidence: 99%